Expanding the Self Brick by Brick: Nonrelational Self-Expansion and Self-Concept Size. (May 2014) - Mattingly, Brent A.; Lewandowski, Gary W.
We conducted three studies to examine whether novel and interesting experiences can expand individuals' self-concepts. In Studies 1 and 2, participants completed measures of experienced self-expansion and self-concept size. Results indicated that participants who had more novel and interesting experiences tended to have larger self-concepts. In Study 3, we employed an embodied cognition manipulation of self-expansion and again measured self-concept size. Results indicated that participants who pulled (vs. pointed to) objects labeled with novel and interesting (vs. nonnovel and uninteresting) activities toward themselves reported larger self-concepts. Additionally, those who pulled novel and interesting (vs. nonnovel and uninteresting) activities reported a larger self-concept. These studies provide the first empirical evidence that nonrelational novel and interesting experiences result in self-concept growth.